Fish & shellfish, grilled & smoked : 300 foolproof recipes for everything from amberjack to whitefish, plus really good rubs, marvelous marinades, sassy sauces, and sumptous sides /: 300 foolproof recipes for everything from amberjack to whitefish, plus really good rubs, marvelous marinades, sassy sauces, and sumptous sides. (©2002) - Unknown
No abstract available